2000
DOI: 10.1177/1541931200044028113
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the Effects of Adding Messages to Warning Labels

Abstract: Within the context of a realistic task (setting up an office space), 84 subjects used a two-drawer file cabinet that displayed a warning label with different numbers of statements—one, three or five. In each of these labels, a target statement, indicating that the bottom drawer was to be filled before the top one to avoid tipping, appeared first in the list. One additional warning label condition had three statements with the target statement appearing last. The warning label was affixed to the file cabinet in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

2002
2002
2019
2019

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(24 citation statements)
references
References 9 publications
1
23
0
Order By: Relevance
“…In an attempt to shed more light on this issue, Frantz et al (2000) had 84 participants use a two-drawer file cabinet that displayed a warning label with different numbers of statements-one, three or five. In each of these labels, a target statement, indicating that the bottom drawer was to be filled before the top one to avoid tipping, appeared first in the list.…”
Section: Introductionmentioning
confidence: 99%
“…In an attempt to shed more light on this issue, Frantz et al (2000) had 84 participants use a two-drawer file cabinet that displayed a warning label with different numbers of statements-one, three or five. In each of these labels, a target statement, indicating that the bottom drawer was to be filled before the top one to avoid tipping, appeared first in the list.…”
Section: Introductionmentioning
confidence: 99%
“…Procedure. In this study, we replicated the experimental design used by Frantz and Rhoades (1993); Frantz et al (2000); and in the second study of Shaver et al (2006). Participants were told that the purpose of the experiment was to analyze how people arrange their work space.…”
Section: Methodsmentioning
confidence: 99%
“…Participants were randomly assigned to one of six warning label design conditions (see Figure 1). For approximately half (53.44%) of the observations, a 3.8 cm × 12.7 cm warning label with a 1 cm flap warning label was affixed to the front of the file cabinet drawers and wrapped around the side of the file cabinet, consistent with Shaver et al (2006) and Frantz et al (2000). For the rest of the observations, the label was placed on a cardboard bridge across the inside of the top drawer.…”
Section: Methodsmentioning
confidence: 99%
“…Warnings are most effective when they are presented proximate (in time and space) to the hazard. Frantz, Rhoades, Young & Schiller, (2000) found that 98% of participants noticed a warning that was located on the physical object associated with the task. The placement of warnings included with product instructions has been shown to influence their effectiveness.…”
Section: Placement and Layout Of Warning Informationmentioning
confidence: 99%